(untitled) (Boulder, Lodon, 1984)
The origins of this book lie in an earlier project. It was executed by me and some junior colleagues at the University of Southern California for the same program in the National Science Foundation that eventually supported the work found in this book.
Keywords: Marine resources,Tài nguyên biển; Government policy,Chính sách của chính phủ; Japan,Nhật Bản